A Brief Guide for the Creation of Author-specific Citation Metrics and Publication Data Using the Thomson Reuters Web of Science and Scopus Databases - Frank Mueller-Langer; Michael Gerstenberger; Julian Hackinger; Benjamin Heisig (Rat für Sozial- und Wirtschaftsdaten (RatSWD), 2013)
The objective of this guide is twofold. First, it shall enable interested readers to understand and reproduce the process of collecting author-specific citation metrics and publication data from the Thomson Reuters Web of Science and Scopus databases that is adopted in Andreoli-Versbach and Mueller-Langer (2013). Second, it presents the problems faced during the data collection process and the refined method of data collection we adopt to address related concerns. Thereby, it may serve interested readers as a guideline to accurately and efficiently retrieve citation metrics and publication information from Thomson Reuters Web of Science and Scopus in similar endeavors.
Keywords: C80; 330; Citation metrics; publication data; Thomson Reuters Web of Science; Scopus